Comparative study of different steganographic techniques - Zeki, Akram M.; Ibrahim, Adamu A.; A. Manaf, Azizah; Abdullah, Shahidan M. (2011)
Steganography is the method of hiding data in such a way that no one, except the sender and the intended recipient, expects the existence of the hidden data. Thus the goal here is always to conceal the very existence of the secret data embedded in an innocent data in such a way that it will be undetectable, robust and the innocent data should be able to accommodate high capacity of the secret data. When it comes to the pro and cons of various Steganographic software, many have been designed; each of them has different features and capabilities for data hiding, hence, this makes it a wide and attractive field for further research, in which the establishment of innovative methods and techniques could be done. Different Steganographic techniques were studied; experiment was carried out using five Steganographic software. Finally comparison was done using benchmarking tool for identifying different performance aspects of the Steganographic techniques and Steganographic software like visual quality, performance indices, memory requirement and the evaluation of the maximum capacity for each software under this study. Experimental results show that all the software under this study performs above optimal level, although there are some differences of features and capabilities observed.